2015
DOI: 10.4236/aces.2015.54048
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Linear Alkylbenzene Sulfonate (LAS) by Immobilized <i>Pseudomonas</i> sp.

Abstract: Anionic surfactants are the most widely exploited chemical surfactants, which are being incorporated into majority of detergents and cleaning products used for household and industrial applications. Linear alkylbenzene sulfonates (LAS) is one of the major xenobiotic anionic surfactants. Biodegradation is an effective process to reduce the amount of surfactants released in the environment. In this study soil samples were collected from detergent contaminated sites to isolate linear alkylbenzene sulphonate degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Jiang et al [15] and Ying [12] mention that concentrations higher than 0.1 mg/L induce chronic toxicity and bioaccumulation in plants [1,4,16]; in the same way this sewage can cause harm or destruction to the root cell membrane, changes in membrane permeability, in fine structure and effects on physiological processes such as photosynthesis [7]. Although, LAS requires at least 4 days for completely degradation [10], twice of this time is necessary in soil under aerobic conditions [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang et al [15] and Ying [12] mention that concentrations higher than 0.1 mg/L induce chronic toxicity and bioaccumulation in plants [1,4,16]; in the same way this sewage can cause harm or destruction to the root cell membrane, changes in membrane permeability, in fine structure and effects on physiological processes such as photosynthesis [7]. Although, LAS requires at least 4 days for completely degradation [10], twice of this time is necessary in soil under aerobic conditions [17].…”
Section: Resultsmentioning
confidence: 99%
“…It has been verified that LAS is aerobically biodegradable in wastewater, and its use is considered environmentally friendly [9]. According to Asok et al [10], more than 90% are rapid biodegraded, approximately within 4 days. In addition, it was observed that biodegradation in absence of oxygen is not favorable [3].…”
Section: -Introductionmentioning
confidence: 99%
“…A detergent is a mixture of surfactants with cleaning properties in dilute solutions. Linear alkyl benzene sulphonates (LAS), alkyl ethoxy sulphates (AES) and alkyl sulphates are the most typically used surfactants in detergents production [3][4][5]. The presence of residual detergents in treated wastewater effluents is common due to its limited decomposability and treatability in typical activated sludge WWTPs [6].…”
Section: Introductionmentioning
confidence: 99%